THE CORRELATION BETWEEN ENGLISH SPEAKING ANXIETY AND STUDENT ACHIEVEMENT AT UNIVERSITAS MUHAMMADIYAH LAMPUNG - Danang Wijayanto; Zohri Hamdani; Dyah Sih Pratiwi (JEELL (Journal of English Education, Linguistics and Literature), 2026)
The purpose of this research was to investigate the impact of English speaking anxiety and academic achievement among second-semester English Education students at Universitas Muhammadiyah Lampung. Despite the recognized importance of speaking skills in EFL contexts, many Indonesian students experience significant anxiety that potentially impacts their academic performance. This research used a quantitative approach. The data were collected from 13 students through the adapted Speech Anxiety Thoughts Inventory (SATI) and speaking assessments evaluated with Brown and Abeywickrama's (2019) rubric. The Pearson correlation analysis showed a strong negative relationship between speaking anxiety and academic achievement (r = -0.876, p = 0.001), with anxiety accounting for 76.7% of the variance in speaking scores. Qualitative analysis of questionnaire responses identified fear of negative evaluation, limited vocabulary, and lack of confidence as primary anxiety sources. While the strong correlation indicates a significant relationship, the study's limitations, including small sample size and correlational design, preclude causal inferences. The finding underscores the need for pedagogical interventions addressing affective factors in language learning and suggests directions for future research with larger samples and experimentally designed.